SOCIO-CULTURAL CHARACTERISTICS OF TERMS RELATED TO HOUSEHOLD APPLIANCES - Akbarova Nargiza Turg`un kizi (Zien Journals, 2022)
This article covers the social-cultural characteristics of terms related to household applications Housing across the world has remained an indispensable phenomenon that affects every facet of humans. Its relevance is so evident that it imparts on man’s socio-physical and mental welfare irrespective of his socioeconomic status, colour or creed. The correct socio-economic position is linked to people seeking inexpensive and decent housing
Keywords: neighbourhood; gender; marital status; ethnicity